An improved whitecap timescale for sea spray aerosol production flux modeling using the discrete whitecap method. Issue 17 (9th September 2013) - Callaghan, Adrian H.
Abstract: [1] The discrete whitecap method (DWM) to model the sea spray aerosol (SSA) production flux explicitly requires a whitecap timescale, which up to now has only considered a whitecap decay timescale, τ decay . A reevaluation of the DWM suggests that the whitecap timescale should account for the total whitecap lifetime ( τ wcap ), which consists of both the formation timescale ( τ form ) and the decay timescale (timescale definitions are given in the text). Here values of τ form for 552 oceanic whitecaps measured at the Martha's Vineyard Coastal Observatory on the east coast of the USA are presented, and added to the corresponding values of τ decay to form 552 whitecap timescales. For the majority of whitecaps, τ form makes up about 20–25% of τ wcap, but this can be as large as 70% depending on the value of τ decay . Furthermore, an area‐weighted mean whitecap timescale for use in the DWM ( τ DWM ) is defined that encompasses the variable nature of individual whitecap lifetimes within a given time period, and is calculated to be 5.3 s for this entire data set. This value is combined with previously published whitecap coverage parameterizations and estimates of SSA particle production per whitecap area to form a size‐resolved SSA production flux parameterization (d F ( r 80 )/dlog10 r 80 ). This parameterization yields integrated sea‐salt mass fluxes that are largely within the range of uncertainty of recent measurements over the size range 0.029 µm <  r 80  < 0.580 µm. Physical factors controlling whitecap lifetime such as bubble plume lifetime and surfactant stabilization are discussed in the context of SSA production from whitecaps. Key Points: Whitecap lifetimes are not constant and vary on a wave by wave basis Whitecap formation timescales contribute 10%‐70% of whitecap lifetime A new discrete whitecap method timescale is defined